Strategi Penggunaan Media Pembelajaran Berbasis Digital dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Fiqih - Baryyah, Khoirul; Sulaiman, M. Sholehuddin; El-Yunusi, M. Yusron Maulana (YASIN, 2025)
This study discusses the strategy of using digital-based learning media in increasing learning motivation in Fiqh subjects. The background of this study is rooted in the need to make learning more interesting and relevant to students. Fiqh subjects often contain abstract and complex concepts, which can be challenging for students to understand and apply in their daily lives. In addition, digital media allows flexibility in learning, gives access to materials anytime and anywhere, and provides real-time feedback which is invaluable to the learning process. All of these contribute to increasing students' learning motivation, making Fiqh learning more interesting and effective. The purpose of the strategy of using digital-based learning media in improving learning motivation in Fiqh subject is to create a more interactive, and relevant learning experience for students. By using digital technology, it is expected that students can more easily understand and apply Fiqh concepts that are often abstract and complex. Digital media allows teachers to present material visually and dynamically through videos, animations and simulations, so that the concepts taught become more concrete and interesting. Strategies For Using Digital-Based Learning Media in Increasing Student Learning Motivation in Fiqh Subjects at Superior Aliyah Madrasah Nur Al Jadid Waru Sidoarjo.